2005
DOI: 10.1063/1.1927539
|View full text |Cite
|
Sign up to set email alerts
|

Convective transport in the scrape-off layer of tokamaks

Abstract: A detailed study of blob formation, dynamics, and the associated convective transport in the scrape-off layer ͑SOL͒ of tokamak plasmas is presented. Dissipation level in the system, in addition to the blob size, is shown to play an important role in determining whether a blob propagates as a coherent object. Nonlinear SOL interchange/ballooning modes are shown to be capable of creating blobs near the separatrix without relying on the core or edge-plasma dynamics. Finally, the SOL density profiles under diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 20 publications
5
80
1
Order By: Relevance
“…[3]. In controlled fusion, this effect is studied in association with the formation of coherent structures (blobs) in the scrape-off layer of tokamak plasmas [4] In geophysics, the observed rocking of the floating bubbles in the equatorial ionospheric F-region is attributed to this effect [5]. Similarly, a zigzag path of magnetic flux tubes emerging in the solar interior, caused by vortex shedding, has been found in numerical simulations [6].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[3]. In controlled fusion, this effect is studied in association with the formation of coherent structures (blobs) in the scrape-off layer of tokamak plasmas [4] In geophysics, the observed rocking of the floating bubbles in the equatorial ionospheric F-region is attributed to this effect [5]. Similarly, a zigzag path of magnetic flux tubes emerging in the solar interior, caused by vortex shedding, has been found in numerical simulations [6].…”
mentioning
confidence: 95%
“…However, the results obtained can be easily applied to other relevant plasma systems by straightforward renormalisation. Equations (1)(2)(3)(4)(5) are numerically solved with the use of the Lagrangian-remap code Lare2d [15]. In our studies we simulate the plasma dynamics in a domain …”
mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] During their radial propagation, the blob-like structures develop a steep front and a trailing wake, which can also be observed in numerical simulations of isolated blob structures [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and simulations of scrape-off layer turbulence. [51][52][53][54][55][56][57][58][59][60][61] Conditional averaging of experimental measurement data have shown that large-amplitude fluctuations are well described by an exponential wave form.…”
Section: Introductionmentioning
confidence: 99%
“…(38) and (43), respectively. In order to demonstrate this, the frequency spectra for two elementary pulse functions will be reviewed.…”
Section: A Derivatives and Discontinuitiesmentioning
confidence: 99%
“…Following [9], we introduce here the typical blob size [34] and velocity [35]: The linear size of each blob in the radial and poloidal direction, a r and a q , are computed as the HWHM of the density fluctuation n r t n r t n r , , , , ,…”
Section: Characterization Of the Blob Size And Shapementioning
confidence: 99%